Architettura fascista nell’epoca democratica post-bellica in Italia: Una breve introduzione - De Vettor, Luisa (Verbum – Analecta Neolatina, 2016)
There are hundreds of buildings scattered around in Italy with a certain common trait, the fascist architecture. An architecture which was one of the main propaganda models and ways of communication of a destructive dictatorial regime lead by Benito Mussolini. The purpose of the article is to try to understand the possible legacy of Italian fascist architecture in contemporary culture and society. We will evaluate how much the meanings of these relics have changed since the time of their construction, and how much time has been necessary to look at these Fascist relics with an eye finally detached from their original dramatic relationship with the dictatorial regime.